Training Need Analysis for the Development of Digital Skills with Competency Certification in the Digital Era: A Study of University Students and Employees in Jakarta, Indonesia - Cedaryana, C.; Indah DM, Devita Restu; Putri, Icha Vanida (Golden Ratio of Human Resource Management, 2025)
Technological advancements in the Digital era demand adaptive digital competencies from university students and employees. This study aims to analyze digital training needs and the role of competency certification, particularly from the National Professional Certification Agency (BNSP), in enhancing workforce readiness. A qualitative descriptive method was employed using data triangulation through closed-ended questionnaires with 100 respondents, in-depth interviews with 10 participants, and document analysis of training materials. The findings indicate that most respondents recognize the importance of digital skills such as Microsoft Office and data processing. Competency certification improves credibility and competitiveness, especially in financial management, human resource management, and digital marketing. However, challenges remain, including limited training infrastructure, low proficiency in advanced digital tools, and financial barriers. The study recommends stronger institutional support for competency-based training and certification facilitation to bridge digital skill gaps in the digital era.